Safely Managed Sanitation in High-Density Rural Areas : Turning Fecal Sludge into a Resource through Innovative Waste Management - Verhagen, Joep (World Bank, Washington, DC, 2019)
Safely managed sanitation is a focus of the SDGs and central to stunting reduction and early childhood survival, both identified by the World Bank's Human Capital Index as critical for humans to develop their full potential. In 2015, 4.5 billion people lacked access to safely managed sanitation. This paper finds that hundreds of millions more people are exposed to significant health risks due to unsafely managed sanitation. This report explores the challenges of fecal sludge management (FSM) in densely populated rural areas and it presents some typical current practices, examples of financially sustainable FSM services, and global innovations in waste management with potential replicability for FSM. Its aim is to promote dialogue on how to move from the Millennium Development Goals' approach to rural sanitation—effectively, building toilets—to the Sustainable Development Goals' approach: safely managed sanitation systems. The paper concludes that the sanitation service chain spans both private and public goods, and market mechanisms are not always adequate to mitigate the safety risks. Public funding will be needed to cover the affordability gap and address safely managed sanitation, requiring a clear and long-term commitment and support from government. The case is similar to that for networked sanitation: without public support, improving the safety of existing FSM services is likely to decrease profit margins and potentially render businesses unviable.